PENGARUH PURSED LIPS BREATHING TERHADAP PEAK EXPIRATORY FLOW RATE PENDERITA PENYAKIT PARU OBSTRUKSI KRONIS - Emdat Suprayitno (Wiraraja Medika : Jurnal Kesehatan, 2017)
Chronic obstructive pulmonary disease (COPD) is a public health problem. Shortness of breath is a major problem on patient COPD. The shortness of breath caused decrease of PEF value. The intervention can be done to patients COPD is pursed lips breathing exercise. The method of this research was true experiment, pretest-posttest design with control group involving 30 respondents with random sampling. Treatment group were 15 respondents that provided PLB exercise three times a week for 4 weeks. Control group were 15 respondents that only getting standard treatment from the hospital. Data analysis was performed with paired t test test and independent t test. The results of paired t test on PEF value are p=0.000 for intervention group and p=0.334 for control groups. The result of independent t test in intervention and control groups PEF value p= 0.000. There was influence pursed lips breathing exercise to increased PEF value. There was difference PEF value on treatment group and control group after pursed lips breathing exercise